2006
DOI: 10.1037/0022-006x.74.3.500
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of girls' and boys' aggressive-disruptive behavior trajectories across elementary school: Prediction to young adult antisocial outcomes.

Abstract: Multiple group analysis and general growth mixture modeling was used to determine whether aggressive-disruptive behavior trajectories during elementary school, and their association with young adulthood antisocial outcomes, vary by gender. Participants were assessed longitudinally beginning at age 6 as part of an evaluation of 2 school-based preventive programs. Two analogous trajectories were found for girls and boys: chronic high aggression-disruption (CHAD) and stable low aggressiondisruption (LAD). A 3rd c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
134
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 48 publications
10
134
3
Order By: Relevance
“…Unlike Schaeffer et al [2006], we found similar percentages of boys and girls in the persistently high aggression trajectory (19 and 15%, respectively, in the pooled GMM), whereas they found a substantially higher percentage of boys than girls in a similar persistent aggression-disruption class. This difference may be attributable to the younger elementary school sample studied by Schaeffer and colleagues.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Unlike Schaeffer et al [2006], we found similar percentages of boys and girls in the persistently high aggression trajectory (19 and 15%, respectively, in the pooled GMM), whereas they found a substantially higher percentage of boys than girls in a similar persistent aggression-disruption class. This difference may be attributable to the younger elementary school sample studied by Schaeffer and colleagues.…”
Section: Discussioncontrasting
confidence: 74%
“…Using latent GMM, we identified four distinct developmental trajectories over a 5-year period from early to late adolescence. Three of these trajectories-Low/No Aggression, Desisting Aggression, and Persistent High Aggression-have been identified in prior developmental studies [e.g., Brame et al, 2001;Broidy et al, 2003;Schaeffer et al, 2006]. The fourth trajectory, Adolescent Aggression, is consistent with developmental theory [e.g., Loeber and Stouthamer-Loeber, 1998;Moffitt, 1993;Patterson and Yoerger, 1993] but has not typically been found in past studies.…”
Section: Discussionmentioning
confidence: 74%
“…In recent years, LGMM has been successfully used to identify longitudinal patterns of adjustment in relation to a wide variety of life events and circumstances, including drinking among college students (Greenbaum, Del Boca, Darkes, Wang, & Goldman, 2005), childhood aggression (Schaeffer et al, 2006;Schaeffer, Petras, Ialongo, Poduska, & Kellam, 2003), retirement in late life (Pinquart & Schindler, 2007), life-threatening medical procedures (Deshields et al, 2006;Lam et al, 2010), and traumatic injury (deRoonCassini et al, 2010).…”
Section: Latent Growth Mixture Modelingmentioning
confidence: 99%
“…In a similar application, Morin et al (2011) used GMM to assess fluctuations in elevated levels of anxiety for adolescents over time and reported five latent classes representing different patterns of anxiety. Finally, Schaeffer et al (2006) used GMM to model patterns of aggression and disruptive behavior in children throughout elementary school years; they found three substantively different latent classes for boys and girls.…”
mentioning
confidence: 99%